(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Among Russia’s most well-known authors, Anton Chekhov skilfully and profoundly captured society and character, hence transcending the limits of realism. Beyond the rigid narrative lines of his day, Chekhov’s works examine the unstated tensions, fleeting emotions, and apparently tiny minutiae of daily life to uncover enormous discoveries about human existence. Usually reflecting the natural flow of life, his stories embrace uncertainty and open-endedness, therefore avoiding definite answers. Through his brief but evocative language, Chekhov captures the psychological subtleties of each, so presenting his characters—not as relics but rather as complex, flawed, and quite real people. His writings at the same time offer a prism through which one may see the social dynamics of late 19th-century Russia, including concerns of class conflict, the fall of traditional institutions, and the existential dilemmas of people living in a country swiftly modernising. Analysing great works like "The Lady with the Dog" and "The Cherry Orchard," this essay explores Chekhovian realism’s continuing relevance as well as its influence on 20th-century literature and modern discourse. Chekhov is a forerunner of modern realism since he can mix the personal and the universal, the subtle and the great, so highlighting the complexity of human nature and society development.